Analisis Efektivitas Signage untuk Meningkatkan Navigasi Penumpang di Terminal Keberangkatan Bandar Udara Fatmawati Soekarno Bengkulu - Amirah, Nisrina Najla; Putra, Iwansyah; Sutiyo (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2025)
Airport information facilities are crucial in supporting operational activities and services, one of which is signage. This study specifically examines the implementation of signage at the departure terminal of Fatmawati Soekarno Airport in Bengkulu, namely operational signage, public facilities, and concession signage. This study uses a descriptive qualitative research method, with data collection techniques in the form of observation, documentation, and interviews. The results of the study indicate that three points of signage at the departure terminal do not meet standards in terms of size, color, and direction of the signs used. As a result, passengers experience confusion and even difficulty in finding locations/facilities in the departure terminal area. This study contributes to evaluating the implementation of signage at the departure terminal, while also providing an integrated service solution in the form of a digital map to improve the effectiveness of information at Fatmawati Soekarno Airport in Bengkulu.